ATM down-regulation is associated with poor prognosis in sporadic breast carcinomas - Bueno, R. C. [UNESP]; Canevari, R. A.; Villacis, R. A. R. [UNESP]; Domingues, Maria Aparecida Custódio [UNESP]; Caldeira, J. R. F.; Rocha, R. M.; Linde, Sandra Aparecida Drigo [UNESP]; Rogatto, Silvia Regina [UNESP] (Oxford University Press, 2014)
Background: Ataxia telangiectasia-mutated (ATM) gene downexpression has been reported in sporadic breast carcinomas (BC); however, the prognostic value and mechanisms of ATM deregulation remain unclear.Patients and methods: ATM and miRNAs (miR-26a, miR-26b, miR-203, miR-421, miR-664, miR-576-5p and miR-18a) expression levels were evaluated by quantitative real-time PCR (RT-qPCR) in 52 BC and 3 normal breast samples. ATM protein expression was assessed by immunohistochemistry in 968 BC and 35 adjacent normal breast tissues. ATM copy number alteration was detected by array comparative genomic hybridization (aCGH) in 42 tumours.Results: Low ATM levels were associated with tumour grade. Absence of ATM protein expression was associated with distant metastasis (P < 0.001), reduced disease-free survival (DFS, P < 0.001) and cancer-specific survival (CSS, P < 0.001). Multivariate analysis indicated ATM protein expression as an independent prognostic marker for DFS (P = 0.001, HR = 0.579) and CSS (P = 0.001, HR = 0.554). ATM copy number loss was detected in 12% of tumours and associated with lower mRNA levels. miR-421 over-expression was detected in 36.5% of cases which exhibit lower ATM transcript levels (P = 0.075, r = -0.249).Conclusions: The data suggest that ATM protein expression is an independent prognostic marker in sporadic BC. Gene copy number loss and miR-421 over-expression may be involved in ATM deregulation in BC.
Keywords: ataxia-telangiectasia-mutated (ATM) gene; breast cancer; copy number alteration; microRNA; prognostic marker